The archives in Rouanet Law - Cunha, Catherine da Silva; Constante, Sônia Elisabete (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
The aim of the article is to discuss the recognition by archivists and archival institutions of the cultural aspect as an important tool for the preservation of documents. It is based on studies about historical and cultural heritage, whose paradigms comprise the Archives as places of memory. It highlights the inclusion of public and private Archives among the cultural areas benefited by the law for cultural promotion, provided these institutions do not restrict access to the public. We also stress the relevance of this integration for the development of cultural projects aimed at preserving documents, as well as raising the necessary resources for their implementation. We point out the relationship between the Archives and Culture established in theoretical references in this field. This study is guided by the polysemous character of the concept of “culture” due its numerous appropriations and applications. We also present the concepts of public policies and cultural projects and conclude that the inclusion of this subject in the curricula of the courses in Archive Administration in Brazil can disseminate tax legislation and ways to raise funds to support Brazilian culture, promote heritage education within the universities and institutions, and contribute to the archiving practice by acknowledging the importance of Archives to culture. Keywords: Archives. Culture. Documentary preservation. Law for cultural promotion. Link para o texto completo (PDF) http://periodicos.puc-campinas.edu.br/seer/index.php/transinfo/article/view/2076/1771